Light-Harvesting Complex Protein LHCBM9 Is Critical for Photosystem II Activity and Hydrogen Production in Chlamydomonas reinhardtii . Issue 4 (4th April 2014) - Grewe, Sabrina; Ballottari, Matteo; Alcocer, Marcelo; D'Andrea, Cosimo; Blifernez-Klassen, Olga; Hankamer, Ben; Mussgnug, Jan H.; Bassi, Roberto; Kruse, Olaf
Abstract : This work analyzes and elucidates the function of the LHC protein isoform LHCBM9. It provides evidence that the green microalga C. reinhardtii has evolved a LHCII-dependent, medium-term process for photoprotection during environmental stress conditions. Abstract: Photosynthetic organisms developed multiple strategies for balancing light-harvesting versus intracellular energy utilization to survive ever-changing environmental conditions. The light-harvesting complex (LHC ) protein family is of paramount importance for this function and can form light-harvesting pigment protein complexes. In this work, we describe detailed analyses of the photosystem II (PSII ) LHC protein LHCBM9 of the microalga Chlamydomonas reinhardtii in terms of expression kinetics, localization, and function. In contrast to most LHC members described before, LHCBM9 expression was determined to be very low during standard cell cultivation but strongly increased as a response to specific stress conditions, e.g., when nutrient availability was limited. LHCBM9 was localized as part of PSII supercomplexes but was not found in association with photosystem I complexes. Knockdown cell lines with 50 to 70% reduced amounts of LHCBM9 showed reduced photosynthetic activity upon illumination and severe perturbation of hydrogen production activity. Functional analysis, performed on isolated PSII supercomplexes and recombinant LHCBM9 proteins, demonstrated that presence of LHCBM9 resulted in faster chlorophyll fluorescence decay and reduced production of singlet oxygen, indicating upgraded photoprotection. We conclude that LHCBM9 has a special role within the family of LHCII proteins and serves an important protective function during stress conditions by promoting efficient light energy dissipation and stabilizing PSII supercomplexes.